Appcast: a low stress and high stretch overlay protocol. (17th May 2005) - Radha, V.; Gulati, Ved P.; Pujari, Arun K.
With IP Multicast not gaining wide acceptance, researchers turned to alternative multicast mechanisms like application level multicast. Application level multicast protocols arrange the participating hosts into an overlay topology; maintain it and distribute data packets over that topology. In this paper, we propose a new application level multicast protocol, describe a few well-known protocols, simulate the protocols and compare the results.